DETERMINANTS OF LOYALTY EMPLOYEE OF AUTOMOTIVE DEALERSHIP - Mondini, Vanessa Edy Dagnoni; Machado, Denise Del Prá Netto; Scarpin, Marcia Regina Santiago; Borges, Gustavo da Rosa (Contextus - Revista Contemporânea de Economia e Gestão, 2015)
The objective of this study was to analyze what determines the loyalty of employees of automotive dealerships. The determinants of loyalty are the proposals dimensions in the studies of Bates et al. (1995): relation to coordination, relationship with supervisors, rewards offered by the company, group problem solving, proximity to the leadership, centralization of power in the company and the company's philosophy. For this analysis, we carried out a descriptive and quantitative study with 151 employees seven car dealerships located in the city of Blumenau. By means of multiple linear regression, it was found that the investigated items, only the company's philosophy and problem solving in teams contribute to the loyalty of the employee to the company.